ALLEGORY AS A RESEARCH OBJECT OF LINGUISTICS (Scientific journal of the Fergana State University, 2024)
Generally, allegorical metaphor, which is widely used in literary studies, is rarely studied in linguistics. There has been and continues to be much discussion and debate about allegory. Through this article, we tried to reveal when allegory appeared in linguistics and its importance in linguistics. Allegory is defined in many scientific literatures as a figurative expression of the values of existence that were widespread in the Middle Ages and the Renaissance. [1, 53-56] Looking at the origin of the term allegory and its history, this term was first mentioned in Roman rhetoric in Cicero‘s treatise "Orator". According to his interpretation, allegory includes the concepts of tralatio, i.e. transfer, metaphor, and he emphasized that "...the flow of numerous metaphors" (fluxerunt continuae plures tralationes) [2, 54] is the basis for the emergence of allegory. This idea caused the term allegory to become widespread in rhetoric later and to be understood in this interpretation.